MECHANISMS OF SPASMOLYTIC ACTIVITY OF ENTEROCIN - PRASHANT BABARAO SHAMKUWAR, (International Journal of Pharma and Bio Sciences, 2013)
Parasympathetic stimulation and histamine increases general gut activity. Parasympathetic nervous system, mediates its action in the gut by stimulation of muscarinic receptors and nicotinic receptors. Histamine causes contraction of smooth muscle of the alimentary tract. An antidiarrhoeal herbal formulation, Enterocin was tested on spontaneous contractions of isolated guinea pig ileum and contractions induced by acetyl choline, nicotine, and histamine in isolated guinea pig ileum. Enterocin decreased the spontaneous contractions of isolated guinea pig ileum and also inhibited the acetyl choline, nicotine and histamine induced contractions of isolated guinea pig ileum. It indicates that spasmolytic effect of Enterocin may be through ganglionic and histamine receptors but not through the muscarinic receptors.